2019
DOI: 10.25011/cim.v42i3.33091
|View full text |Cite
|
Sign up to set email alerts
|

Energy spectrum computed tomography improves the differentiation between benign and malignant solitary pulmonary nodules

Abstract: Purpose: To evaluate the diagnostic efficiency of computed tomography (CT) values at the 40~140 keV monochromatic level for the differential diagnosis of solitary pulmonary nodules (SPNs). Methods: Energy spectrum CT data of 44 patients with SPNs were analyzed retrospectively; 24 patients with malignant SPNs served as the malignant group and 20 patients with benign SPNs served as the benign group. The basic material concentration and the enhancement degree differences in double-phase enhance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…To the best of our knowledge, this is the first study to use “one-stop” spectral and perfusion scanning and to compare the diagnostic effectiveness of these two imaging methods. Both spectral and perfusion CT imaging types can distinguish benign from malignant tumors ( 32 ), especially chest tumors ( 14 , 15 , 19 , 33 , 34 ). However, previously reported estimates of diagnostic efficacy have been inconsistent, and the conclusions remain subject to debate.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study to use “one-stop” spectral and perfusion scanning and to compare the diagnostic effectiveness of these two imaging methods. Both spectral and perfusion CT imaging types can distinguish benign from malignant tumors ( 32 ), especially chest tumors ( 14 , 15 , 19 , 33 , 34 ). However, previously reported estimates of diagnostic efficacy have been inconsistent, and the conclusions remain subject to debate.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike traditional CT, spectral CT decomposes the traditional polyenergetic X-ray beam into continuous single energies ranging from 40 to 140 KeV, which may achieve qualitative separation and quantitative determination of substances. [31][32][33][34][35][36] For example, Metin et al 31 found that the conspicuity of primary breast cancer was significantly higher in low KeV virtual monochromatic images. Thus, the combination of spectral CT and high-Z nanomaterials shows potential for the accurate diagnosis of various diseases.…”
Section: Introductionmentioning
confidence: 99%